THE ADMINISTRATION OF STEM EDUCATION IN SECONDARY SCHOOL OF SECONDARY EDUCATIONAL SERVICE AREA OFFICE 4 - Ketbamrung, Anchalee (Journal of Buddhist Anthropology, 2021)
The objectives of this research article were to study the administration conditions, to develop and to evaluate the administration of STEM Education in secondary school of secondary education service area office 4. This research was a qualitative research. Research methods consisted of three phases. Phase 1 was the study of the administration conditions of STEM Education in secondary school of secondary education service area office 4. The research instrument for data collection was a questionnaire. The sample consisted of 169 people and interviewed 9 senior experts. Phase 2 was developing the administration of STEM Education in secondary school of secondary education service area office 4 by applying the concepts, theories and related research including the study of empirical data and the interviews obtained from the study in phase 1 were used as information for building the model to develop the administration of STEM Education in secondary school of secondary education service area office 4. After that, evaluating the validity and suitability by 5 experts by using in-depth interview. Phase 3 was Assessing the usefulness and feasibility of the application of the model. The research instrument for data collection was a questionnaire and the sample consisted of 169 people. The data were analyzed both quantitative and qualitative. The results show that 1) the overall and each aspect, the administration conditions of STEM Education in secondary school of secondary education service area office 4 was at a high level. 2) The administration of STEM Education in secondary school of secondary education service area office 4 comprised 2 factors as follows: 1) Deming cycle which consisted of the following subfactors: 1) job planning (plan) 2) action operations (do). 3) auditing (check) 4) editing (act). 2) STEM learning management which consisted of the following subfactors:1 teaching by project 2) integrated learning 3) problem - solving scenario design. 3) Evaluation Results showed that the administration of STEM Education in secondary school of secondary education service area office 4 in overall benefits and possibilities was at the highest level.